Propuesta de nueva metodología cualitativa para el estudio de las teorías implícitas docentes - De La Cruz Rodríguez, Rodri Demus (2018)
This report presents the results of an investigation that explored teachers' implicit theories about mathematics assessment. For this purpose, a qualitative methodology was used, combiningcontingency analysis for text content analysis and automated graphical representation through Pathfinder Associative Networks to highlight the main categories of analysis obtained and their relationship. The participants were 87 teachers in initial training; for the exploration of implicit theories, the implicit theories theoretical framework was taken as the theoretical framework. Data collection was carried out using the narrative technique in which the participants were asked to write down their perceptions of mathematics assessment. The results indicate that the use of this methodology is appropriate for the study of teachers' implicit theories; it helps to obtain data with a minimum intervention of the researcher and can be applied to multiple research topics. In addition, it is evident that the implicit theories held by the teachers of the participating Peruvian university are better related to traditional pedagogy and the implicit theories held by the teachers of the Spanish university are closer to contemporary pedagogy.